Strategi Transisi Kabupaten Purworejo dari E-Government menuju Smart City - Murhadi Murhadi; Hamid M. Jumasa (APIC, 2019)
Starting in 2018 Purworejo district will implement governance by following the smart city system. Purworejo Government has been very serious about the planning and implementation plan of smart cities in Purworejo Regency. In the Regional Medium-Term Development Plan (RPJMD) 2016-2021, which still projects e-government based governance, there is the term cyber city to support the implementation of more effective and efficient city governance. The transition process from e-government to smart city needs to be pursued so that the planning contained in the RPJMD can work in synergy with the Garuda Smart City Model (GSCM) adopted by Purworejo district. The transition method used is to link the programs contained in the RPJMD with the service domain, namely smart economy, smart society, and smart environment.